The Martingale hypothesis in the Mexican stock market - de la Uz, Nadiezhda (Estudios Económicos de El Colegio de México, 2002)
We examine the martingale hypothesis for the Mexican stock market during the period 1993 - 2000. This research includes 97% of all securities with medium and high trading frequency. The proposed tests are robust when dealing with non normal and heteroskedastic data. The tests use the fact that the variances from continuously compounded returns are lineal in time. The hypothesis is not rejected for the main Mexican stock indexes (the IPC and the INMEX). For individual stocks we find that in 70% of the examined cases, the hypothesis is not rejected. Finally, we include proofs of long- range independence, which are required for the derivation of the relevant statistics.